Training exercises, match demands, and variability in elite futsal - Ribeiro, João Nuno; Ferraz, António; Gonçalves, Bruno; Serrano, Carlos; Coutinho, Diogo; Ballester, Rafael; Travassos, Bruno (Frontiers in Sports and Active Living, 2025)
IntroductionUnderstanding the physical demands of different training exercises is crucial for optimizing athlete performance. This study aims to compare high-intensity activities across different training exercises and official match-play scenarios. The analysis focuses on performance variations across training exercises and the variability observed within each format.MethodsAn observational study was conducted on a team competing in the 1st Division of the Spanish futsal league over three consecutive seasons. The training and match sessions were organized into mid-court exercises (20 × 20 m), three-quarters court exercises (28 × 20 m), and full-court exercises (40 × 20 m) and match.ResultsResults showed that the full court exercises presented the more demanding results, and the mid court exercises the less demanding results of external load for both acceleration, deceleration and sprints. The comparison between the training exercises and the match revealed distinct physical demands variability across exercise categories. Mid-court training exercises exhibited significantly higher variability compared to all other training formats and match scenarios. In contrast, match conditions demonstrated the lowest variability.DiscussionFindings highlight the importance of understanding the physical demands of each training exercise to balance intensity, variability, and contextual relevance to tailor training programs that ultimately optimizing athlete preparation for the multifaceted demands of competitive play.